Pengaruh Substitusi Tepung Tapioka dengan Tepung Singkong (Manihot esculenta) terhadap Mutu Organoleptik Bakso Ayam - Hendrik, Hendrik; Lunatri, Andi (MACROCEPHALON : Jurnal Ilmu Peternakan, 2024)
This study aimed to determine the effect of substituting tapioca flour with cassava flour on the organoleptic quality of chicken meatballs. The experiment was conducted using a Completely Randomized Design (CRD) consisting of 5 treatments and 4 replications. The treatments were substitution levels of tapioca flour with cassava flour, namely A = 0% (control), B = 25%, C = 50%, D = 75%, and E = 100%. The parameters observed included organoleptic tests covering color, taste, aroma, and texture, which were evaluated by semi-trained panelists using a hedonic scale. The results showed that cassava flour substitution had a significant effect on the organoleptic quality of chicken meatballs. The treatment with a 50% substitution level (C) obtained the highest scores across all parameters, particularly in texture and chewiness, and was preferred compared to other treatments. Substitution levels above 75% tended to decrease the organoleptic quality, producing a coarser texture and a less desirable aroma. Therefore, the use of cassava flour as a tapioca substitute up to a level of 50% can be applied as an economical alternative raw material while maintaining the organoleptic quality of chicken meatballs.